The Role of Husband and Wife in Maintaining Family Resilience: Study of Takhrij Hadith - Maesaroh, Siti; Sutisna, Nata (Journal of Takhrij Al-Hadith, 2025)
This study aims to discuss the hadith about the role of husbands and wives in maintaining resilience. This research uses a qualitative approach by applying the descriptive-analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about the role of husbands and wives in maintaining family resilience in an-Nasa'i's narration No. 2536. The results and discussion of this study indicate that the status of the Hadith is of Shahih quality. This study concludes that the Hadith narrated by An-Nasa'i No. 2536 shows that Islam provides flexible guidelines regarding the roles of husbands and wives, with an emphasis on cooperation, communication, and responsibility according to their respective abilities. In addition, career women are not a threat to family resilience, but rather an opportunity to improve family welfare, provided that husbands and wives are able to maintain a balance of their respective roles. Synergy and agreement between couples is the main key in building a harmonious and resilient family.